2021
DOI: 10.1177/26317745211051834
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of endoscopic therapy for Barrett’s esophagus

Abstract: Barrett’s esophagus is the condition in which a metaplastic columnar epithelium replaces the stratified squamous epithelium that normally lines the distal esophagus. The condition develops as a consequence of chronic gastroesophageal reflux disease and predisposes the patient to the development of esophageal adenocarcinoma. The diagnosis and management of Barrett’s esophagus have undergone dramatic changes over the years and continue to evolve today. Endoscopic eradication therapy has revolutionized the manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…Chest pain, dysphagia, and general post-procedure discomfort were other adverse events commonly reported by patients. Generally, pain and dysphagia occurred 3-4 days post-procedure [ 11 - 13 ]. In our study, chest pain and dysphagia were reported in 17 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Chest pain, dysphagia, and general post-procedure discomfort were other adverse events commonly reported by patients. Generally, pain and dysphagia occurred 3-4 days post-procedure [ 11 - 13 ]. In our study, chest pain and dysphagia were reported in 17 cases.…”
Section: Discussionmentioning
confidence: 99%
“…BE is the most-known risk factor for the development of EAC, and the risk of EAC is greater by about 30-fold or more among patients with BE compared to that for the general population [ 14 , 15 ]. BE occurs when the normal squamous epithelium of the distal esophagus ( Figure 1 a–c) changes to columnar-lined intestinal-type cells ( Figure 2 a,b), which can usually be seen when the mucosa of the esophagus is repeatedly exposed to gastric acid [ 16 , 17 , 18 ]. Other risk factors for the development of BE are male gender, age, race, smoking, alcohol consumption, and obesity [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopy has been essential in the detection of lesions suspicious for esophageal cancer and tissue acquisition to make an accurate histologic diagnosis [ 6 ]. As our understanding improves regarding precancerous lesions such as Barrett’s esophagus (BE), a known precursor of EAC, endoscopy has promoted early detection, surveillance, and prevention of progression [ 7 ]. Furthermore, advances in technology have increased the therapeutic applications of endoscopy in curative resection of early cancer and palliation of advanced malignancy.…”
Section: Introductionmentioning
confidence: 99%